Hubungan Status Gizi dengan Usia Menarche pada Siswi Sekolah Dasar Kelas 4, 5 dan 6 di Sekolah Dasar Negeri Grabahan Kecamatan Karangrejo Kabupaten Magetan. - Sumini Sumini (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2014)
Public Elementary School District Grabahan Karangrejo Magetan on 5 November 2013 found the total number of 45 students. Of the 85% who are menstruating got 7 of them feel uneasy first menstrual period and 3 of them mersakan pain at first menstrual period and 5 of them have not experienced menstruasi.Dari interviewed 15 girls there that have good nutrition and malnutrition that affects their menarche , the situation can be seen from the shape of their body that looks thin and there is visible fat. The purpose of this research to determine the nutritional status of relations with the age of menarche in girls primary school grade 4, 5 and 6 at the Elementary School District Grabahan Karangrejo Magetan.This research is quantitative analytical research studies with correlational approach, this study used a form of